The Impact of Male Participation in Gender Based Violence Programing in Mudzi District: A Case Study of Wards 14. - Juma, Blessing M. (2017)
This study is aimed at assessing the impact of male participation in gender based violence prevention programs. A case study of Ward 14 in Mudzi district was used. The study targeted initiatives that were programmed to make men take active participation as strategy to stop gender based violence. A reduction of the number of cases as the impact was being assessed. 180 respondents managed to take part in the research and all filled in questionnaires which were semi-structured with sections A, B, C and D. A total number of 84 males and 96 female answered questions in the questionnaire. 6 interviews were carried out , 4 NGO representative and 2 government department officers , one from the police (VFU )and one from the ministry of women affairs gender and community development (MWAGCD). The interview guides were structured in a way that they would show the activities of the organizations in the area, the rate of male participation, the impact that the programs have and some of the reasons that are reventing males from fully participating in the programs. The results were that men are gradually taking interest in involving in gender based violence prevention programs, although there are challenges from the part of men themselves and from the part of NGOs.